Between the Past and Future. Antwerp Zoo and the 19th Century Belgium - Song, Zihao (Technium Social Sciences Journal, 2022)
Antwerp zoo was established in 1843 under the management of the Zoological Society of Antwerp. As one of the oldest zoos in Belgium and Europe, the establishment, operation and development of Antwerp Zoo are closely related to Belgian society in the 19th century. At the same time, it also reflects the self-awareness of the newly independent Belgians in the face of industrial civilization and exotic nature. This article discusses how the Antwerp Zoo as a public place embodies 19th century Belgian colonial and imperial ideas from perspectives of function, architecture, visitors and animals and the cultural meaning of modern zoos in European continent. Modern European zoos represented by Antwerp zoo are social and educational places dominated by the middle class in the 19th century, and also reflect people’s thought about the relationship between human and nature.